A culpa na separação e no divórcio - Vera, Mercedes Cristina Rodrigues (2008)
According to current legislation, partnerships and conjugal relations may be amicable or litigious dissolved. Since 04 Jan 2007 and after some requirements filled out, a couple that intends a divorce or an amicable separation has the extrajudicial formality as another option for reaching their aim. During the search for the roots of divorce and separation guilt, an introspection in canon and roman laws was realized. Modern law was reached as Middle Age ended. The family law received a severe influence from the protestant reform and as consequence, the secularization of law and a definitive separation of State and Church took place. In the research of guilt evolution in matrimony dissolution and under the paternal system, the first regulations were initiated, when the matrimony was still considered an indissolvable institution, and after, the divorce maked the relation rupture possible Before the promulgation of the Federal Constitution in 1988 an analysis of guilt was realized, facing the fundamental principle of human dignity and its reflex in matrimony dissolutions as well as the strengthening of the idea of conjugal life rupture and the weakness of guilt idea for judicial separations motivation. In this context, a doctrinal debate takes place considering the convenience of the guilt maintenance in the national juridical system. This questioning grows in importance as the consequences of guilt elimination in family law are analyzed, and the possibility to litigate the reparation of damages eventually suffered from the violation of matrimony duties, and understood as a necessary illicit act in the configuration of civil responsibility for moral and material damages. We may conclude by saying that the guilt strong presence in the separation acts motivation is unfeasible, at least in this present moment, for its total elimination from the national juridical scenario